马来西亚6至7岁华族儿童的三语词汇习得研究 = A study of the lexical acquisition by Malaysia trilingual children aged 6-7 - 林欣儿 Lim, Jingle (2019)
马来西亚邻近于新加坡，但是两国从文化、教育政策上还是相差很大。新加坡政府极力融合各个民族，让英语成为各民族的通用语。相比之下，马来西亚各民族缺乏这种“过度语言”，所以各民族必须晓得对方的语言才能进行沟通。这也造就了马来西亚华人通晓三语的特殊现象。然而，马来西亚华人对于三语的掌握如何？是否存在着语言发展不平衡的情况？这些是值得深入研究的问题。本研究分成问卷调查、词汇量测试及正式测试三部分。研究结果显示：（一）儿童词汇量发展与年龄和性别有一定直接的关系。（二）三语儿童在华语和英语的习得上会比马来语较好，其中以华语的习得量为最高，英语其次，词汇习得量最少的是马来语。（三）语言接触方式、家庭用语等对语言习得构成一定的影响。（四）儿童对三语的同步掌握相对双语儿童或单语儿童困难些，儿童会因无法兼顾三者而导致三语发展落差大。希望本研究能为马来西亚语言习得尽一份贡献，为父母与教育者提供教育参考，以便对马来西亚儿童的语言发展有更进一步的了解。 Malaysia is close to Singapore, but its culture and education policies still have a great difference. Singapore government is trying to integrate all ethnic groups and English has become the lingua franca of all nations. In contrast, there is no single common language in Malaysia, and thus all ethnic groups must be familiar with all three of Malaysia’ main languages in order to communicate. This has created a special phenomenon in which most Malaysian Chinese are trilingual. However, how do Malaysian Chinese master these three languages? Is there a situation in which language development is unbalanced? These are issues that deserve further study. The study is divided into three parts: questionnaire survey, vocabulary test and formal test. The results of the study show that: (1) The development of the children's vocabulary has a direct relationship with age and gender. (2) The trilingual children were better at learning Chinese and English than Malay. Their Chinese test result was the highest, followed by English, and the least was the Malay language. (3) Language contact methods and family language have a certain impact on language acquisition. (4) The trilingual children's simultaneous learning of language was more difficult than that of the bilingual children or monolingual children. Trilingual children also exhibited an inability to achieve balance among all three languages. It is hoped that this study will contribute to a better understanding of the acquisition of language in Malaysia, and provide educational references for parents and educators concerned with the language development of Malaysian children.